A Strategy Map Model to Improve The Efficiency of Indonesian Banks - Mulyana, Rahmat; Achsani, Noer Azam; Andati, Trias; Maulana, Tubagus N.A. (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study approaches the problem of banking efficiency in an innovative way. It aims to identify workable solutions for enhancing the efficiency of Indonesian banks as something that is very important after this pandemic Covid-19 time. In order to build a strategy map model, the research is divided into four steps: (1) a desk study of best practices for enhancing banking efficiency; (2) a survey for choosing strategies; (3) a focus group discussion to identify relationships among strategies; and (4) an Analytic Network Process (ANP) modeling to prioritize and build a strategy map model. According to the Strategy Map, the following areas should be prioritized for efficiency improvement: Financial, Customer Value, Learning and Growth, and Internal Process. Indonesian bankers could allocate limited resources in ways that would boost the efficiency of the majority of banks based on the designed strategy map. Despite the fact that these strategy maps are not universal, the research shows that the suggested method is a practical and objective way to create more justified strategy maps. Keywords: banking efficiency, bank performance, efficiency strategy, strategy map, ANP